Increased pathogenicity of pneumococcal serotype 1 is driven by rapid autolysis and release of pneumolysin - Laura C. Jacques (Nature Portfolio, 2020)
The mechanisms behind the high invasiveness of Streptococcus pneumoniae serotype 1 are unclear. Here, Jacques et al. show that this feature is due to overproduction and rapid release of pneumolysin, which induces cytotoxicity and breakdown of tight junctions, allowing rapid bacterial dissemination from the respiratory tract into the blood.